A functional and probiotic approach: mixed fruit juice powder with addition of lactobacilli - RIVEROS, Ana Laura Rotela; SOUZA, Michelle Maria Barreto de; VIEIRA, Thaís Regina Rodrigues; SANTANA, Anderson Andrade de; MORAIS, Jasiel Santos de; GROSSO, Carlos Raimundo Ferreira; MACIEL, Maria Inês Sucupira (Food Science and Technology, 2024)
The aim of this study was to evaluate changes in a mixture of acerola and ciriguela juice (40/60%, respectively) and the juice mixture supplemented with Lactobacillus rhamnosus LPAA 01, L. casei LPAA 02, and L. plantarum LPAA 03, ratio 1:1, both powders obtained by spray drying, during storage. The stability of acerola and ciriguela mixed powder without the addition of microorganisms was evaluated for 90 days at 25°C in different water activities (Aws) (0.11, 0.23, and 0.34). Aw that most effectively maintained the stability of mixed powdered juice was used for the evaluation of the fermented mixed juice powder containing probiotics for 45 days at 5 and 25°C, respectively. Samples were characterized by physicochemical properties, bioactive compounds, and cell viability. The physicochemical properties of the powdered mixed juice without the addition of probiotics remained stable when stored at 25°C at an Aw of 0.11 for 60 days. Ascorbic acid, carotenoids, and total phenolics showed favorable characteristics for the commercialization and bioactive properties of the powders, with potential use as functional ingredients in food. Probiotic powders showed viable cell counts above 6.0 log colony-forming units (CFU)/g after storage for up to 20 days at 5°C and up to 14 days at 25°C.